Estudo dos parâmetros plaquetários em pacientes portadores de malária sintomática causada pelo Plasmodium Vivax - Santos, Fábio Alexandre Leal dos (2013)
In the last years, an increasing occurrence of severe and complicated Plasmodium vivax malaria has been reported. So, is important to study all the aspects related to this disease, traditionally regarded as benign. The aim of this study was to describe the frequency and factors associated with changes of platelet indices in patients with symptomatic P. vivax infection. Records of patients attended at the Malaria Outpatient Clinic of the Júlio Müller Hospital (UFMT) since 2002 were analysed if a complete blood countwas performed at the first visit. Data were tabulated and analyzed for clinical, epidemiological and hematological characteristics, with emphasis on platelet indices. 172 patients that had complete clinical and laboratory information were included. We found a great variability in the values of the mean platelet volume (MPV), the platelet distribution width (PDW) and the plateletcrit (PCT). There was also a negative association between VPM and PDW with the time living in an endemic area (p=0,004 and p <0,001, respectively). A negative association was also observed between the PDW and previous episodes of malaria (p=0.013). And a negative and statistically significant association was observed between parasitemia and plateletcrit (p<0.001). After adjustment by multivariate logistic regression, it was found that the presence of warning signs for severe and complicated malaria remained independently associated with changes in MPV and PDW. Despite of platelet indices are associated with criteria for severe malaria definition and they are used as a risk factor for several diseases, including heart disease, information that relate them to malaria are scarce. Once these parameters are directly related to platelet function, these findings confirm previous observations that the MPV and PDW are potential markers of inflammation and may be useful in the prognostic evaluation of patients with infection by P. vivax. Multiple Plasmodium infections in the past were associated to the reduction of MPV and PDW, perhaps as a result of the acquisition of clinical immunity by individuals chronically exposed to malaria transmission. Our findings suggest that quantitative changes in platelet indices are associated with more severe P. vivax infections and these changes are less common in individuals with successive exposure to malaria transmission, probably explained by the development of clinical immunity. However, the benefit of using platelet indices in clinical practice should be confirm in further studies, using appropriate methodology.